Somatostatin in inflammatory bowel disease - J. D. Van Bergeijk; J. H. P. Wilson (Mediators of Inflammation)
Intestinal inflammation is controlled by various immunomodulating cells, interacting by molecular mediators. Neuropeptides, released by enteric nerve cells and neuroendocrine mucosa cells, are able to affect several aspects of the general and intestinal immune system, with both pro- as well as anti-inflammatory activities. In inflammatory bowel disease (IBD) there is both morphological as well as experimental evidence for involvement of neuropeptides in the pathogenesis. Somatostatin is the main inhibitory peptide in inflammatory processes, and its possible role in IBD is discussed.